جدلية المبنى والمعنى في التوقيعات العباسية - قوراري السعيد (جامعة الوادي - University of Eloued, 2025)
اتسعت أفاق الفكر والثقافة في العصر العباسي ونشطت حركه الترجمة والتأليف وامتدت في كل شيء يمكن أن يخطر على البال، فتطورت الكتابة في ذلك العصر أدت إلى ظهور جنس جديد في الأدب العربي أطلق عليه "التوقيع"، فهذا النوع كان موجودا في العصر الإسلامي والعصر الأموي لكنه ازدهر أكثر في العصر العباسي، وأنشئ له ديوان خاص سمي بديوان التوقيعات وعُيَّن كبار الكتاب والأدباء والبارعون. وقد جرت عادة الملوك والولاة من الفرس أن يوقعوا على القصص بعبارة بليغة، أو حكمه حكيمة، يتخير لها أحسن اللفظ وأجود المعنى. The horizons of thought and culture expanded in the Abbasid era, and the movement of translation and writing became active and expanded in everything that could come to mind. Writing developed in that era led to the emergence of a new genre Arabic literature called “signature.” This genre was present in the Islamic era and the Umayyad era, but it He flourished more during the Abbasid era, and a special diwan was established for him, called the Diwan of Signatures, and senior writers, authors, and adepts in were appointed. It was customary for Persian kings and rulers to sign stories with a figurative phrase, or wise wisdom,for which the best pronunciation and the finest meaning were chosen.
مقال .مجلة علوم اللغة العربية وآدابها. مج 17. ع 02
Keywords: الثقافة; التوقيع; العصر العباسي; الديوان; الملوك; culture; signature; Abbasid era; the Diwan; kings